Nursing Diagnoses in Pediatric Surgical Inpatients: A Cross-Sectional Study - Gita Adelia; Eka Malfasari; Deswinda Deswinda; Candra Saputra; Bayu Azhar; M Zul 'irfan; Rizka Febtrina; Noni Ramadianty (Nursing Current: Jurnal Keperawatan, 2026)
Introduction: Children in surgical units are vulnerable to nursing problems due to invasive procedures and complex medical conditions. Identifying nursing diagnoses is essential to determine appropriate and effective interventions.Objective: This study aimed to identify nursing diagnoses based on the Indonesian Nursing Diagnosis Standards (Standar Diagnostik Keperawatan Indonesia, SDKI) in pediatric patients hospitalized in a pediatric surgical care unit. Methods: This quantitative study employed a cross-sectional design using retrospective data from medical records. The study was conducted in the Pediatric Surgical Care Unit of Arifin Achmad General Hospital, Riau Province, from December 2024 to March 2025. The sample consisted of 107 children and adolescents who were hospitalized for more than 24 hours. Data were collected using pediatric nursing assessment forms and analyzed descriptively using frequency and percentage. Results: A total of 13 actual nursing problems were identified. The most common problem was acute pain (D.0077), found in 82 cases (75%). Other issues included decreased intracranial adaptive capacity (D.0066) and constipation (D.0049), each in 6 cases (6.5%), as well as urinary elimination impairment (D.0040) and anxiety (D.0080), each in 2 cases (2.2%). Conclusion: Acute pain is the most dominant nursing problem among postoperative children, accompanied by anxiety as a significant psychological issue. A systematic SDKI-based assessment of pain and anxiety, along with integrated interventions encompassing pain management and anxiety reduction, is essential to improve the quality of care and enhance postoperative recovery outcomes in children.